Ανάπτυξη συστήματος Ηλεκτρονικού Επιχειρείν με χρήση της τεχνολογίας Blockchain - (:unkn) unknown (My University, 2024)
The authenticity and security of pharmaceuticals have never been more critical than in today’s complicated global supply chains. The importance of traceability in the pharmaceutical supply chain is prevalent throughout this thesis, discussing demand and applications, feasible options, and improvements via groundbreaking technologies. The first chapter defines the case for supply chain management and explores the complexities and demands for traceability from the pharmaceutical supply chain. Subsequently, the second chapter explains how innovative technologies are rising to the traceability challenges and introduces Blockchain technology, which presents a potential answer for improving drug traceability by explaining its underlying theory, and potential applications. The remaining chapters describe the development and deployment of an application written in Python programming language, which demonstrates the use of Blockchain in a traceability scenario along with a front-end web application using Flask to enhance its use-case. Through experimentation, this research demonstrates the capabilities of Blockchain technology in bolstering traceability within the pharmaceutical domain. Finally, the thesis concludes with insightful reflections on the key findings along with areas for improvement in the developed application.
Keywords: Εφοδιαστική Αλυσίδα, Φαρμακευτική Εφοδιαστική Αλυσίδα, Ιχνηλασιμότητα, Blockchain, Pharma 4.0; Supply Chain, Pharmaceutical Supply Chain (PSC), Traceability, Blockchain, Distributed Ledger Technology (DLT), Pharma 4.0